Novel role of FTO in regulation of gut–brain communication via Desulfovibrio fairfieldensis-produced hydrogen sulfide under arsenic exposure - Ruonan Chen; Xiaoqin Chai; Yunxiao Zhang; Tianxiu Zhou; Yinyin Xia; Xuejun Jiang; Bo Lv; Jun Zhang; Lixiao Zhou; Xin Tian; Ruonan Wang; Lejiao Mao; et al. (Gut Microbes, 2025)
Fat mass and obesity-associated protein (FTO) is the key demethylase that reverses the abnormally altered N6-methyladenosine (m6A) modification in eukaryotic cells under environmental pollutants exposure. Arsenic is an environmental metalloid and can cause severe symptoms in human mainly through drinking water. However, there is no specific treatment for its toxic effects due to the uncovered mechanisms. We previously revealed that exposure to arsenic increased the level of m6A via down-regulation of FTO, which might serve as a potential target for intervention against arsenic-related disorders. In this study, our results demonstrated that chronic exposure to arsenic significantly disrupted the intestinal barrier and microenvironment. Also, this administration resulted in the enhancement of m6A modification and the reduction of FTO expression in the intestine. By using both CRISPR/Cas9-based FTO knock-in strategy and adeno-associated virus (AAV)-mediated overexpression of FTO in the intestine, we established for the first time that up-regulation of FTO remarkably ameliorated arsenic-induced disruption of intestinal barriers and altered microenvironment of mice. We also firstly identified a dominant gut microbial species, Desulfovibrio fairfieldensis, which was sharply reduced in arsenic-exposed mice, was able to proceed arsenic-induced neurobehavioral impairments by declining the levels of its major metabolite hydrogen sulfide. Administration of Desulfovibrio fairfieldensis could significantly alleviate the neurotoxicity of arsenic. Intriguingly, the beneficial effects of FTO against arsenic neurotoxicity possibly occurred through a novel gut–brain communication via Desulfovibrio fairfieldensis and its produced hydrogen sulfide. Collectively, these findings will provide new ideas for understanding the mechanisms of arsenic-induced toxic effects from a gut–brain communication perspective, and will assist the development of explicit intervention strategy via regulation of a new potential target FTO for prevention and treatment against arsenic-related both intestinal and neurological disorders.